Multifaceted roles for BCL3 in cancer: a proto-oncogene comes of age - Gillian Seaton; Hannah Smith; Andrea Brancale; Andrew D. Westwell; Richard Clarkson (Molecular Cancer, 2024)
Abstract In the early 1990’s a group of unrelated genes were identified from the sites of recurring translocations in B-cell lymphomas. Despite sharing the nomenclature ‘Bcl’, and an association with blood-borne cancer, these genes have unrelated functions. Of these genes, BCL2 is best known as a key cancer target involved in the regulation of caspases and other cell viability mechanisms. BCL3 on the other hand was originally identified as a non-canonical regulator of NF-kB transcription factor pathways – a signaling mechanism associated with important cell outcomes including many of the hallmarks of cancer. Most of the early investigations into BCL3 function have since focused on its role in NF-kB mediated cell proliferation, inflammation/immunity and cancer. However, recent evidence is coming to light that this protein directly interacts with and modulates a number of other signaling pathways including DNA damage repair, WNT/β-catenin, AKT, TGFβ/SMAD3 and STAT3 – all of which have key roles in cancer development, metastatic progression and treatment of solid tumours. Here we review the direct evidence demonstrating BCL3’s central role in a transcriptional network of signaling pathways that modulate cancer biology and treatment response in a range of solid tumour types and propose common mechanisms of action of BCL3 which may be exploited in the future to target its oncogenic effects for patient benefit.